Laser hair removal after surgery vs. surgery alone for the treatment of pilonidal cysts: a retrospective case–control study. (17th July 2018) - Kelati, A.; Lagrange, S.; Le Duff, F.; Lacour, J.‐P.; Benasaid, R.; Breaud, J.; Passeron, T.
Abstract: Background: Based on the presumed role of hair in pilonidal cyst (PNC) pathogenesis, laser epilation has been used to decrease recurrences. However, most of the data rely on case reports and uncontrolled series, and the rare controlled studies reported conflicting results. The objective of this study was to investigate the efficacy of laser hair removal (LHR) to decrease the recurrence rate after surgery of PNC vs. surgery alone. Methods: We conducted a retrospective monocentric case–control study in the departments of Pediatric Surgery and Laser Center of Dermatology of the University Hospital of Nice in France from January 2010 to June 2017. We included all patients with PNC who had surgery during the period, and we compared patients who had LHR after surgery to those having surgery alone. The main outcome was the prevalence and number of recurrences of PNC in each group. Results: Twelve patients – eight treated with alexandrite laser and four patients with Nd : YAG – were included in the cases group; 29 patients treated with surgery alone were included in the control group. The mean and the median number of laser sessions were 4.2 and 5, respectively (extremes 1–10). The postsurgical recurrence rate without LHR was 51.7%, and their number varied from 1 to 3. A significant decrease in the recurrence rate was observed after LHR (8.3%) compared to control group ( P < 0.001). The median duration before recurrence was 14 months for surgery alone. The median follow‐up was 18 months (1–30 months) for LHR group and 30 months (6–72 months) for surgery alone group. Two patients had abnormal healing or persistent sinus after surgery alone compared to none in the group who undergone laser procedure after surgery. Conclusions: Laser hair removal decreases the risk of delayed healing and of recurrences of PNL after surgical procedure.